2021
DOI: 10.1242/jeb.240861
|View full text |Cite
|
Sign up to set email alerts
|

Bumblebees can detect floral humidity

Abstract: Floral humidity, a region of elevated humidity in the headspace of the flower, occurs in many plant species and may add to their multimodal floral displays. So far, the ability to detect and respond to floral humidity cues has been only established for hawkmoths when they locate and extract nectar while hovering in front of some moth-pollinated flowers. To test whether floral humidity can be used by other more widespread generalist pollinators, we designed artificial flowers that presented biologically-relevan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 93 publications
(233 reference statements)
0
31
0
Order By: Relevance
“…The bees would typically extend the proboscis while they landed, therefore we did not analyse any landing or drinking responses. In the final part of the approach, just prior to landing, the bees’ antennae came close or even in contact with the nib, and we must assume that they possibly see it and sense the humidity from sucrose solution in the small opening ( Harrap et al, 2021 ). We therefore excluded any data points closer than 0.5 cm from the analysis of the trajectory data.…”
Section: Methodsmentioning
confidence: 99%
“…The bees would typically extend the proboscis while they landed, therefore we did not analyse any landing or drinking responses. In the final part of the approach, just prior to landing, the bees’ antennae came close or even in contact with the nib, and we must assume that they possibly see it and sense the humidity from sucrose solution in the small opening ( Harrap et al, 2021 ). We therefore excluded any data points closer than 0.5 cm from the analysis of the trajectory data.…”
Section: Methodsmentioning
confidence: 99%
“…and California poppy Eschscholzia californica Cham.. These species are appropriate choices for demonstrating the role of transpiration in floral humidity generation, as both produce larger amounts of floral humidity compared to other flower species (Harrap et al 2020a ) comparable to levels which have been demonstrated to be able to influence pollinator foraging decisions (von Arx et al 2012 ; von Arx 2013 ; Wolfin et al 2018 ; Harrap et al 2021 ). E. californica has been identified (along with other poppies) to produce little in the way of nectar rewards (Hicks et al 2016 ), and so nectar evaporation is unlikely to explain E. californica humidity production.…”
Section: Methodsmentioning
confidence: 99%
“…Floral humidity, as part of this multimodal floral display, can influence pollinator foraging decisions. Hawkmoths (von Arx et al 2012 ), bumblebees (Harrap et al 2021 ), and flies (Nordström et al 2017 ) have innate preferences for flowers that produce higher floral humidity intensities when they are able to choose between flowers producing differing intensities. Furthermore, floral humidity differences between flowers, regardless of whether elevated rewards are associated with higher floral humidity production or not, can aid bumblebee learning of rewarding flowers (Harrap et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations